2021
DOI: 10.4103/picr.picr_148_19
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of an educational program to promote research ethics in undergraduate medical students

Abstract: Background: MBBS students lack training in research ethics which is crucial when they enter clinical practice and venture into clinical research in future. This study was planned to implement an educational module to build concepts in research ethics Objective: To assess the change in the knowledge and attitude of medical students towards research ethics. Methods: The study was initiated after obtaining institutional ethics committee approval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…A similar learner-centered approach in teaching research ethics through small group discussions on ethics-based case scenarios has been tried by other investigators. [ 3 4 5 ] These studies prove that innovative short training sessions in research ethics improved the participants’ knowledge, attitude, and skills.…”
Section: Discussionmentioning
confidence: 78%
“…A similar learner-centered approach in teaching research ethics through small group discussions on ethics-based case scenarios has been tried by other investigators. [ 3 4 5 ] These studies prove that innovative short training sessions in research ethics improved the participants’ knowledge, attitude, and skills.…”
Section: Discussionmentioning
confidence: 78%
“…Postgraduate students are an essential group, as they must understand the ethical aspects of research early in their education. This will help them conduct safe and responsible research throughout their careers [19]. Cases of research misconduct, violations of research ethics and integrity, and ethically questionable behavior are frequently reported [20].…”
Section: Ethics Committeesmentioning
confidence: 99%
“…As Patel et al examined, use of case studies and discussions about the information being taught promotes a “better understanding of ethical practices and its [sic] importance in conducting research” [ 18 ]. Structuring class sessions based on focused module-by-module layout, such that one module was “small group case-based training” and one module was “theme lectures,” was effective in ensuring that learning objectives were achieved and survey data indicated that along with group discussions this type of learning was particularly effective [ 18 ]. Research education is fundamental to establishing RECR and research mentoring best practices at institutions of higher learning and is relevant to nearly every discipline supported by NSF—especially STEM research fields [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%